2013
DOI: 10.35790/ebm.1.3.2013.3582
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lamanya Diabetes Melitus Terhadap Terjadinya Disfungsi Ereksi

Abstract: Diabetes mellitus is a condition with excess glucose in the blood which can lead to complications such as chronic diseases, among others cardiovascular disease and sexual dysfunction such as erectile dysfunction. This study aimed to determine the effect of duration of diabetes mellitus on the occurrence of erectile dysfunction. This was an analytic survey with cross sectional study design. Samples were 30 respondents, taken by simple random sampling. Data were collected by using a questionnaire IIEF-5 (Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
4
0
7
Order By: Relevance
“…17 Vascular dysfunction due to hypertension could lead to disruption of blood flow and clitoral function as erectile organs in women. 26 High blood pressure could be a causal factor for a person's low sexual passion.…”
Section: Resultsmentioning
confidence: 99%
“…17 Vascular dysfunction due to hypertension could lead to disruption of blood flow and clitoral function as erectile organs in women. 26 High blood pressure could be a causal factor for a person's low sexual passion.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 70-80% vascular problems in DM patients who experience ED are strongly associated with atherosclerosis. Furthermore, occlusion of cavernous arteries also contributes to long-term sexual problems [8].…”
Section: Discussionmentioning
confidence: 99%
“…Other research reported a significant correlation between the duration for which patients experience DM and an incidence of ED. ED occurred to 63.3% patients who have been experiencing DM for 5-8 years while 36.7% patients with 1-4 years of DM also had ED [8]. There is only a limited number of studies indicating the correlation between age, duration of DM, HbA1c levels, and ED at primary facilities in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…10 (2) Diabetes Mellitus (DM), gula darah dalam tubuh yang tidak terkontrol dapat merusak sel-sel sarah, pembuluh darah dan menyebabkan disfungsi endotel. 11 (3) Hipertensi, pada pasien hipertensi fungsi endotelium tidak mampu menghasilkan dilatasi penis, sehingga mengakibatkan penurunan persistensi ereksi. 12 (4) Obesitas, pada pria obesitas terjadi kerusakan pada endotelium dan perubahan hormon testosteron menjadi estrogen.…”
Section: Pendahuluanunclassified
“…Apabila Nitrit Oksida (NO) tidak dihasilkan akan menyebabkan pembuluh darah pada penis sulit melebar yang mengakibatkan aliran darah ke organ erektil berkurang sehingga terjadilah disfungsi ereksi. 11,24,25 Obesitas merupakan faktor risiko penting bagi banyak penyakit umum termasuk disfungsi ereksi. Pada kondisi IMT normal, tidak terjadi peningkatan jaringan adiposa dan pada pria obesitas, leptin akan meningkat sebanding dengan nilai IMT mereka Kadar leptin yang tinggi menginduksi disfungsi endotel, meningkatkan tekanan darah, dan menurunkan produksi testosteron.…”
Section: Hubungan Indeks Massa Tubuh Dengan Disfungsi Ereksiunclassified